Changes in Assortative Matching and Inequality in Income: Evidence for the UK. (21st May 2020) - Chiappori, Pierre‐André; Costa‐Dias, Monica; Crossman, Sam; Meghir, Costas
Abstract: The extent to which like‐with‐like marry is important for inequality as well as for the outcomes of children who result from the union. In this paper, we present evidence on changes in assortative mating and its implications for household inequality in the UK. Our approach contrasts with others in the literature in that it is consistent with an underlying model of the marriage market. We argue that a key advantage of this approach is that it creates a direct connection between changes in assortativeness in marriage and changes in the value of marriage for the various possible matches by education group. Our empirical results do not show a clear direction of change in assortativeness in the UK between the birth cohorts of 1945–54 and 1965–74. We find that changes in assortativeness pushed income inequality up slightly, but that the strong changes in education attainment across the two cohorts contributed to scale down inequality.